Somanathapura, Keshava temple, Sculpture of Lakshmi-Narayana, Lord Vishnu with his consort Goddess Lakshmi; Hoysala architecture - Lawrence Rodrigues (2021)
Image courtesy: Lawrence Rodrigues - www.yatrikaone.com